Some data on the decline of Classical Languages in Secondary and Baccalaureate Education - Almodóvar García, Javier (Avances en Supervisión Educativa, 2025)
For some years now, there has been a worrying decrease in the offer of some of the classical subjects in Secondary schools, which have been pushed out of the education system for a number of different reasons. In order to understand the situation, surveys have been carried out since the 2018-19 academic year, coordinated by the sections of the Spanish Society for Classical Studies (SEEC) and other organizations integrated in the platform Escuela con Clásicos (EcC). The percentage of teachers in Andalusia who have completed the survey for the academic year 2024-25 is so significant that the information obtained is reliable and reflects the real situation in the schools. The conclusions are alarming: the presence of Classical Culture is residual, Greek is living a decline in the educational offer, and Classical Mythology has not managed to be present in a significant number of schools. Only Latin seems, for the moment, to be escaping this decline.
Keywords: Greek (classical); Latin; Classical Culture; Secondary education, curriculum.